A case report of cecal perforation due to Ogilvie syndrome after cesarean section - Behzad Nematihonar; Javad Zebarjady Bagherpour (Mashhad University of Medical Sciences, 2020)
Introduction: Ogilvie syndrome is a non-mechanical and acute colon obstruction that can occur in women after pelvic surgery and can lead to cecal perforation if not be early diagnosed. Therefore, familiarity with this syndrome and its symptoms can help to prevent its complications. In this study, we report a case of ogilvie syndrome which resulted in perforation of the cecum and underwent right hemicolectomy. Case presentation: A 42-year-old woman after 72 hours of cesarean section (second turn) progressively had abdominal distension, obstipation flatulence and abdominal pain. At admission, there were signs of peritoneal stimulation, leukopenia, and electrolyte imbalance. The patient underwent laparotomy and the finding was cecal perforation. Right hemiclectomy was performed. Due to the severe contamination of the abdominal cavity, double barrel ileostomy was done. The patient was sent to surgical intensive care unit and treated with broad-spectrum antibiotics for 3 days. Subsequently, she was transferred to the ward and after the defication, the fluids regimen was started for the patient and discharged from the hospital 12 days after the surgery. And 3 months later she underwent ileostomy closure and did not have any particular medical problems in the subsequent follow-ups. Conclusion: Familiarity with ogilvie syndrome symptoms, including distension and bloating and obstipation, should always be considered by the physicians and personnel. It may be important especially in the presence of a recent history of pelvic surgery, because early diagnosis of this syndrome can be helpful in preventing its complications and mortality.